Pedalling liszt's works on the modern piano - Ernesaks, Mart (Taideyliopisto Sibelius-Akatemia, 2014)
The purpose of this study is to discuss the problems that occur when some of Franz Liszt's original pedal markings are realized on the modern piano. Both the construction and sound of the piano have developed since Liszt's time. Some of Liszt's curious long pedal indications produce an interesting sound effect on instruments built in his time. When these pedal markings are realized on modern pianos the sound is not as clear as on a Liszt-time piano and in some cases it is difficult to recognize all the tones in a passage that includes these pedal markings. The precondition of this study is the respectful following of the pedal indications as scored by the composer. Therefore, the study tries to find means of interpretation (excluding the more frequent change of the pedal), which would help to achieve a clearer sound with the effects of the long pedal on a modern piano. This study considers the factors that create the difference between the sound quality of Liszt-time and modern instruments. Single tones in different registers have been recorded on both pianos for that purpose. The sound signals from the two pianos have been presented in graphic form and an attempt has been made to pinpoint the dissimilarities. In addition, some examples of the long pedal desired by Liszt have been recorded and the sound signals of these examples have been analyzed. The study also deals with certain aspects of the impact of texture and register on the clarity of sound in the case of the long pedal. In conclusion, the study suggests some solutions for reducing unclear sounds on the modern piano.
Keywords: Liszt, Franz.; piano; akustiikka; pedaali; sointi; piano